PENGARUH PEMBERIAN AIR PERASAN JERUK LEMON (CITRUS LIMON) TERHADAP PENURUNAN BERAT BADAN PADA TIKUS JANTAN GALUR WISTAR - QURATUL AINI HAMSI (JURNAL ILMIAH KOHESI, 2021)
Obesity is a disorder that involves excessive body fat. Obesity management aims to lose weight so as to preventcomplications and clinical symptoms due to obesity. Lemon as an alternative to natural ingredients in losing weight. Thisresearch method is an experiment with a pre and post test design group design. The subjects were 32 male rats Rattusnorvegicus that met the inclusion and exclusion criteria divided into two groups, namely the treatment group and the controlgroup. The sampling technique uses the Federer formula. The average body weight before and after the treatment groupwas 208.81 ± 4.792 gr and after 166.15 ± 9.8476 gr. The average body weight before and in the control group was 209.00 ±43.88261 gr and after 218.55 ± 5.8293 gr. There was a significant difference in body weight of male rats Rattus norvegicusbefore and after between the treatment group and the control group (p = 0,000). The influence of lemon extract (citrus limon)on weight loss in male Wistar strain rats.